Predictors of In-Hospital Mortality in Patients with Infective Endocarditis: A Single-Center Study - Hanim, Haifany Fauziyah; Ikhsani, Rizkania; Yudharaputri, Digita Natarina; Cool, Charlotte Johanna; Hasan, Melawati (International Journal of Integrated Health Sciences, 2025)
Background: Infective endocarditis remains a life-threatening condition with high in-hospital mortality, necessitating identification of predictive clinical factors.Objective: To identify predictors of in-hospital mortality in infective endocarditis (IE) patients.Methods: This single-center retrospective study included 88 patients with IE aged ≥ 18 years treated at Dr. Hasan Sadikin General Hospital, Bandung, Indonesia, between September 2019 and May 2023. During hospitalization, data regarding clinical characteristics, blood cultures, and clinical outcomes were assessed to identify the predictors of in-hospital mortality. Data were analyzed using chi-square and binary logistic regression.Results: Among 88 patients with IE, the majority were male (56.8%) and aged < 60 years old (78%). More than two-thirds of patients had valvular heart disease. During treatment, 22 patients (25%) underwent cardiac surgery, and the total in-hospital mortality rate was 35.2%. Although not statistically significant, in-hospital mortality rate was lower in operated patients (22.7% vs 39.4%). In multivariate analysis, septic shock was the only significant predictor of in-hospital mortality (OR 40, 95% CI: 4.7–339, p 0.001)Conclusion: Septic shock is a strong predictor of in-hospital mortality among patients with infective endocarditis. Invasive management by cardiac surgery does not significantly decrease the mortality risk.